MORPHOLOGICAL IDENTIFICATION AND POPULATION OF FRUIT FLY (Bactrocera sp.) (Diptera: Tephritidae) IN CHILI FIELDS, SAVANAJAYA VILLAGE BURU DISTRICT - Hasinu, Jeffij V.; Patty, John A.; Tuhumury, Gratiana N. C. (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2020)
Morphological identification and population of fruit fly (Bactrocera sp.) (Diptera: Tephritidae) in chili fields, SavanajayaVillage Buru District. Fruit fly (Bactrocera sp.) are pests that damage horticultural crops, one of which is chili and has thepotential to reduce the production quality and quantity. The aim of this research was to identify and obtain populationnumbers of fruit fly species in the chili fields in Savanajaya Village, Buru District. This study used diagonal sampling methodwith fruit fly traps placed randomly at each sub location of sampling, traps were modified Steiner ’s Trap type. Each trap wasconsisted of 1.5 mL of methyl eugenol on cotton ball, the treatment was repeated three times. Observations were at 3, 6, 9 and12 days after application (daa). The identification results showed that the fruit flies species that trapped were Bactroceradorsalis (Hendel) and Bactrocera umbrosus (Fabricius). The highest number of fruit fly was trapped at 6 daa with an averageof 110.67 to 134.03 or 48.51 to 58.73% from total catch, in addition the lowest catch was at 12 daa with an average of 29.67 to64.67 or 12.99 to 28. 34%. The average number of trapped population was 914.62 individuals.